Opportunities and obstacles of targeted therapy and immunotherapy in small cell lung cancer. (2nd January 2021) - Yu, Lin; Lai, Qinhuai; Gou, Lantu; Feng, Jiafu; Yang, Jinliang
Abstract: Small cell lung cancer (SCLC) is an aggressive malignant tumour which accounts for approximately 13–15% of all newly diagnosed lung cancer cases. To date, platinum-based chemotherapy are still the first-line treatments for SCLC. However, chemotherapy resistance and systemic toxicity limit the long-term clinical outcome of first-line treatment in SCLC. Recent years, targeted therapy and immunotherapy have made great breakthrough in cancer therapy, and researchers aim to exploit both as a single agent or in combination with chemotherapy to improve the survival of SCLC patients, but limited effectiveness and the adverse events remain the major obstacles in the treatment of SCLC. To overcome these challenges for SCLC therapies, prevention and early diagnosis for this refractory disease is very important. At the same time, we should reveal more information about the pathogenesis of SCLC and the mechanism of drug resistance. Finally, new treatment strategies should also be taken into considerations, such as repurposing drug, optimising of targets, combination therapy strategies or prognostic biomarkers to enhance therapeutic effects and decrease the adverse events rates in SCLC patients. This article will review the molecular biology characteristics of SCLC and discuss the opportunities and obstacles of the current therapy for SCLC patients.